2020
DOI: 10.1038/s41598-020-62149-x
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction and gas chromatography–mass spectrometric determination of probable carcinogen 1,4-dioxane in cosmetic products

Abstract: In the present work, a method based on solvent extraction and gas chromatography-mass spectrometry (GC-MS) has been validated for the determination of 1,4-dioxane in cosmetics. Various solvents including ethyl acetate, hexane, methanol, dichloromethane and acetone have been used for the extraction of 1,4-dioxane, among them the ethyl acetate was found to be the most efficient extracting solvent. This method has offered excellent quality parameters for instance linearity (R 2 > 0.9991), limit of detection (LOD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For example, when comparing 7 g and 3 g of sample with 3 mL of solvent, the extraction yield was 38.9% increased. A similar tendency was found in Park et al's study [24]. In their study, when the recovery rate was tested by adding 1 ppb and We found statistical significance in the correlation between sample weight and extraction yield (Table 3), indicating the higher yield of 1,4-dioxane extraction as more sample weight was added.…”
Section: Optimization Of Extraction Yield Of 14-dioxane Using Respons...supporting
confidence: 89%
See 2 more Smart Citations
“…For example, when comparing 7 g and 3 g of sample with 3 mL of solvent, the extraction yield was 38.9% increased. A similar tendency was found in Park et al's study [24]. In their study, when the recovery rate was tested by adding 1 ppb and We found statistical significance in the correlation between sample weight and extraction yield (Table 3), indicating the higher yield of 1,4-dioxane extraction as more sample weight was added.…”
Section: Optimization Of Extraction Yield Of 14-dioxane Using Respons...supporting
confidence: 89%
“…For example, when comparing 7 g and 3 g of sample with 3 mL of solvent, the extraction yield was 38.9% increased. A similar tendency was found in Park et al's study [24]. In their study, when the recovery rate was tested by adding 1 ppb and 10 ppb 1,4-dioxane to the water sample, the recovery rate increased from 66.8% to 72.3% as methyl tert-butyl ether was used for a solvent and from 86.5% to 101.8% as methylene chloride was used for a solvent, respectively.…”
Section: Optimization Of Extraction Yield Of 14-dioxane Using Respons...supporting
confidence: 85%
See 1 more Smart Citation
“…The standard deviation of zero concentration was obtained by extrapolation and identified as S 0 , which is the signal-to-noise ratio. LOD and LOQ of method were defined as 3S 0 and 10S 0 [31,32], which were 0.0567 and 0.189, respectively. The results are shown in Table 2.…”
Section: Methods Detection Limitmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) leverages the absorption and emission of radio waves by atomic nuclei in an external magnetic field, applicable to organic compounds containing active nuclei (such as 1 H, 13 C), and is instrumental in analyzing the structure of complex organic compounds in cosmetics [ 129 ]. Gas chromatography (GC) employs gas as the mobile phase and separates components through a stationary phase in a chromatography column, ideal for volatile and thermally stable organic compounds like fragrances and solvents in cosmetics [ 130 ]. High-performance liquid chromatography (HPLC) uses a liquid as the mobile phase under high pressure to separate components, is extensively applicable to various organic compounds, including high molecular weight and non-volatile substances, and is used for detecting and analyzing moisturizers, preservatives, vitamins, and other components in cosmetics [ 131 ].…”
Section: Compositions and Representative Compounds Of Cosmeticsmentioning
confidence: 99%